Persepsi karyawan food & beverage culinary terhadap kinerja butcher di hotel six senses uluwatu - Anwar, Adryan Evaldo; Putra, Agus Muriawan; Ariani, Ni Made (Jurnal Kepariwisataan dan Hospitalitas; Vol 5 No 1 (2021): Vol.5,No.1,2021, 2021)
This research is based on guest complaints regarding poor food quality, employees must make new food to handle guest complaints so that kitchen operations are disrupted. Butcher is a section contained in the food & beverage organization, tasked with maintaining food ingredients will later be cooked by employees in charge of the restaurant. The purpose of study was to determine the characteristics of food & beverage culinary employees and perceptions of food & beverage culinary employees on the performance of Butcher in the Six Senses Uluwatu hotel. Data collection methods are observation, interviews, questionnaires, literature study and documentation. The sampling technique uses saturated sampling because all members of the population are used as research samples, namely all employees who work at Rocka and Crudo restaurant with a total of 30 people. The data analysis technique used is descriptive qualitative and quantitative, then the data were analyzed using a Likert scale to determine the perception employees on Butcher performance. The results showed that the perception of culinary employees on the performance of Butcher in the Uluwatu Six Senses hotel was categorized in Good criteria with an average total questionnaire score of 4.09. According to the results of the interview Butcher has followed the applicable duties and responsibilities. However, there are several problems faced by Butcher namely difficulties in recruiting employees who understand food handling, therefore Butcher only uses contract or training employees to complete his work so that when not monitored there are still often errors in food processing.